Community Service : Helping Businesses Grow H. Ridwan By's Tenun Kubang through Business Strategy Development in The Digital Era Besti. (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
H. Ridwan By’s Kubang weaving strives to maintain its existence through digital marketing by using unique traditional motifs and the  distinctiveness  of  Minangkabau motifs  as  a  Minangkabau cultural heritage to local and international communities. By adopting digital technology and design, H. Ridwan By’s Kubang weaving can increase the attractiveness of Minangkabau weaving products, thus reaching a broader market. The research methodology used was observation and interviews with the owner and craftmen of H. Ridwan By’s Kubang weaving. The marketing strategy  used  is  social  media  and  e-commerce  platforms  to increase the visibility and accessibility of Minangkabau weaving products globally. To positively impact the business, expand the market, and introduce the richness of Minangkabau culture to the world.